Implikasi Pandemi Covid-19 terhadap Diplomasi Pertahanan Masyarakat Global dan Regional: Bentuk Kerjasama oleh Organisasi Regional - Waskito, Wasis (Jurnal Diplomasi Pertahanan, 2020)
As of October 29, 2020, WHO stated that Covid-19 had infected more than 43 millionpeople worldwide with 400 thousand new cases every day and had caused more than 1 millionpeople to die. The Covid-19 pandemic has changed the nations’ views of security concept and hasimplications for global and regional communities’ defence diplomacy. This paper uses a contentanalysis research method based on Mayring's theory and focuses on defense diplomacyimplemented by 10 regional security organizations in the world based on Bailes and Cottey’s work,namely AU, Arab League, ASEAN, APEC, CARICOM, EU, OAS, OIC, SADC, and NATO.From the analysis of related content, it can be concluded that the Covid-19 pandemic hasimplications toward the form of defense diplomacy carried out by international organizations.Defense diplomacy carried out during the pandemic focused on the commitment and assistancemade to reduce the spread of Covid-19 and the nations’ economic recovery in the form of healthdiplomacy and economic diplomacy. This is in line with the complexity in the concept of securityand the variety of areas of cooperation that can be accomplished in the concept of defense diplomacy.Keywords: Covid-19 pandemic, defence diplomacy, security, regional organizations